4(8x+8)-12x=4(-11+6x)

Simple and best practice solution for 4(8x+8)-12x=4(-11+6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(8x+8)-12x=4(-11+6x) equation:



4(8x+8)-12x=4(-11+6x)
We move all terms to the left:
4(8x+8)-12x-(4(-11+6x))=0
We add all the numbers together, and all the variables
4(8x+8)-12x-(4(6x-11))=0
We add all the numbers together, and all the variables
-12x+4(8x+8)-(4(6x-11))=0
We multiply parentheses
-12x+32x-(4(6x-11))+32=0
We calculate terms in parentheses: -(4(6x-11)), so:
4(6x-11)
We multiply parentheses
24x-44
Back to the equation:
-(24x-44)
We add all the numbers together, and all the variables
20x-(24x-44)+32=0
We get rid of parentheses
20x-24x+44+32=0
We add all the numbers together, and all the variables
-4x+76=0
We move all terms containing x to the left, all other terms to the right
-4x=-76
x=-76/-4
x=+19

See similar equations:

| |5x-11|=|7x+1| | | 84.6=9.4y | | 5/2+q=1/2 | | 3x+1+5x-6=42 | | 7=x+x-5 | | 3(2x+4)-2x(x+1)=3(2-4x) | | 2−9h=9−10h | | 4x+31x-7=30x+7 | | m-4=12=8 | | 3(6)^x=3888 | | 5/2+q=9/18 | | 2x+(x/2)+(x/4)=297 | | (9/4y)=9 | | 6−8t=-2t | | 3/8f+1/2=6(61/16f-3) | | m-17.18=0 | | 1/6x+2=5/6x-4 | | 16=-7w+3(w+8) | | 1/9y-3=-2 | | 118-5k=9k+6 | | 5z+25=50 | | 13r-4=11r+16 | | 6-0.25=f-4 | | 5+3h=-2h | | 9x+10=7x+20 | | 3/w=54 | | 56x÷7=88 | | z+5=4=9 | | 18x+13=x+149 | | 180-x+80=180 | | 4(4x+55)=5(x+33) | | 10.5t+84=4.5t+36 |

Equations solver categories